PEMANFAATAN TEKNOLOGI INFORMASI UNTUK BRAND REJUVENATION LEMBAGA AL QUR’AN AL FALAH - Achmad Yanu Alif Fianto; Rudi Santoso; Abdullah Khoirriqoh (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2017)
The purpose of this activity is to develop appropriate technology (TTG) for Islamic da'wah activities at the Al Qur'an Al Falah Institute in Surabaya. This is done because Al Qur'an Al Falah Surabaya institution has only run da'wah with conventional methods only and without utilizing the advantages of information technology. The Internet as a product of the latest technology is regarded as the best communicating medium today, ultimately changing the ways of communicating. This is caused by the sophistication of the internet that is able to create ease of communicating to obtain information needed by the community and some form of convenience is realized in social media, video sharing and website. New opportunities to create major positive impacts especially in the field of da'wah; so it becomes a necessity that da'wah activities can also be done by utilizing the sophistication of information technology. The opportunity is broadened by the fact that internet users are increasingly growing over time to become an emerging new potential that continues to grow. One of the parties who should be able to take advantage of the advantages of information technology for good is the institution of the course Al Qur'an Al Falah (LKF).Â Keywords: Website, Social Media, Articles Management